2004
DOI: 10.1111/j.1469-8749.2004.tb00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of prehension in hemiparetic cerebral palsy: similarities and differences between the ipsi‐ and contra‐lesional sides of the body

Abstract: This study aimed at broadening our insight into ipsi-and contra-lesional control of prehension after unilateral brain damage. Six male adults with hemiparetic cerebral palsy (mean age 17 years 3 months, SD 15 months) performed unrestricted grasping of discs that differed in size (40, 60, and 80mm in diameter) and which were placed at different distances from the participants (150mm and 30mm). A precalibrated Optotrak 3020 system was used for recording motion. Kinematics of the transport and grasp component, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 49 publications
2
28
1
Order By: Relevance
“…In one study, the less affected hand showed delayed aperture formation during reach and the more affected hand demonstrated no anticipatory shaping at all (Ronnqvist & Rosblad, 2007), while another cohort of children achieved peak aperture at 90% of reach in both hands, compared to 50% in TD children (Steenberger & van der Kamp, 2004). There are two possible explanations for this discrepancy.…”
Section: Quantifying Deficits In Hand Posture To Object Shapementioning
confidence: 92%
See 3 more Smart Citations
“…In one study, the less affected hand showed delayed aperture formation during reach and the more affected hand demonstrated no anticipatory shaping at all (Ronnqvist & Rosblad, 2007), while another cohort of children achieved peak aperture at 90% of reach in both hands, compared to 50% in TD children (Steenberger & van der Kamp, 2004). There are two possible explanations for this discrepancy.…”
Section: Quantifying Deficits In Hand Posture To Object Shapementioning
confidence: 92%
“…Second, although aperture is correlated with object size, the relationship between shape and hand posture is complex. In prior studies of aperture modulation, the size of similarly shaped cylinders was varied (Jeannerod, 1986;Ronnqvist & Rosblad, 2007;Steenberger & van der Kamp, 2004), whereas our objects were similar in size, but varied in shape. Thus, prior studies reflect aperture control for size accommodation rather than shape.…”
Section: Quantifying Deficits In Hand Posture To Object Shapementioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, bimanual tasks require complex spatial-temporal coordination that has been shown to be impaired in children with hemiplegia. 30,32,43 Transcallosal transmission between hemispheres, which appears to be implicated in spatial coupling between the limbs, 44 may be altered in individuals with hemiplegia. 45 This means that in addition to specific lesions affecting their involved upper extremity, there may be functional brain damage that limits bimanual coordination.…”
Section: Developing Bimanual Habits In Children With Hemiplegiamentioning
confidence: 99%